Pengaruh Servant Leadership terhadap Nilai Kinerja Guru - Bakry Bakry; Syamril Syamril (Universitas Negeri Malang, 2020)
Abstract: Servant leadership is a form of leadership which is oriented to serve the needs of subordinates in order to improve their pay scale. The term of servant leadership was first introduced by Robert K. Greenleaf in 1970. Servant leadership can be implemented in educational institution. School as one of those intuition that runs teaching and learning process is highly determined by the practices of servant leadership performed by the principal. This research aims at investigating the effect of servant leadership on teachers and employees at Sekolah Islam Athirah Makassar. This is a quantitative research using regression analysis in analyzing the data. The variables of this research are servant leadership (X) and teachers and employees grade performance (Y). The total participant is 90 which was taken randomly from each unit including primary school (SD), junior high school (SMP), and senior high school (SMA). The result of regression analysis showed that there was significant effect by0,02 < 0,05. It can be concluded that the X variable has effect on Y variable. In addition, it is obtained that t-test is higher than t-table (2.297 > 1.991) which means Ho is rejected and there is effect of servant leadership on teachers and employees’ performance grade. The regression equation obtained is Y = 76,058 + 0,187 X. Abstrak: Servant leadership atau kepemimpinan yang melayani adalah konsep kepemimpinan yang pertama kali diperkenalkan oleh Greenleaf (1970) yang dimaksudkan sebagai bentuk kepemimpinan yang berorientasi pada sifat melayani kepentingan bawahan agar mereka menjadi lebih sejahtera. Praktik kepemimpinan yang melayani (servant leadership) juga dapat dilaksanakan pada institusi pendidikan. Sekolah sebagai institusi pendidikan yang menjalankan proses pendidikan dan pembelajaran bagi peserta didik sangat ditentukan oleh praktik kepemimpinan yang dijalankan oleh kepala sekolah. Penelitian ini bertujuan menganalisis pengaruh kepemimpinan yang melayani (servant leadership) terhadap kinerja guru dan karyawan di Sekolah Islam Athirah Makassar. Metode penelitian kuantitatif dengan menggunakan analisis regresi, variabel penelitian adalah servant leadership (X) dan nilai kinerja guru dan karyawan (Y), jumlah sampel sebanyak 90 orang guru dari unit SD, SMP dan SMA. Bedasarakan analisis regresi diperoleh nilai signifikan 0,02 < 0,05 sehingga disimpulkan bahwa variabel x berpengaruh terhadap variabel Y. Pada nilai t diperoleh thitung > ttabel (2,297 > 1,991) sehingga H0 ditolak artinya ada pengaruh servant leadership terhadap nilai kinerja guru dan karyawan. Dengan Persamaan Regresi yang terbentuk adalah Y = 76,058 + 0,187 X.